The Influence of NCT 127 Brand Ambassador Usage on Nu Green Tea Purchase Decision through Brand Awareness as an Intervening Variable among NCTzen Malang" - Febrian, Hans; Wahyono, Seno Aji; Rohim, Yasin Nur (International Journal of Business and Applied Economics, 2024)
This study aimed to investigate the impact of the NCT 127 brand ambassador on purchase decisions, with brand awareness serving as a mediating factor. This study used a descriptive causal approach to explore how the NCT 127 brand ambassador affects purchase decisions, mediated by brand awareness. It focused on NCT 127 fans in Malang City, with a 100-person sample determined using the Cochran formula. Analyses included instrument, classical assumption tests, path analysis, coefficient of determination, and partial t-tests. The results show the brand ambassador significantly impacts brand awareness (<0.05), positively affecting purchase decisions. Path analysis indicates 84% of decisions link to brand awareness and the ambassador, confirming brand awareness' mediating role.